Measurement of CaO-SiO2-SaCl2 slag density by an improved Archimedean method - Wang Y.; Morita K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In order to optimize the removal of boron during the refining of slag to obtain solar grade silicon, the density of molten slag was measured by an improved Archimedean method within a temperature range from 1073 to 1373 K. It was found that the density of molten slag at 1723 K can be deduced by linear fitting, and that the slag density decreases with increasing temperature. However, a reduction in slag density occurs with decreasing CaO concentration. An increase in the molar volume of slag was also observed with increasing temperature.